Community Service: Developing Web-Based Interactive Digital Books to Improve Learning Outcomes at MIN 2 Palangka Raya - Arif Dian Pratama; Rahmat Rahmat; Zaitun Qamariah (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
This collaborative community service activity aims to improve the learning outcomes of grade IV students at MIN 2 Palangka Raya City using web-based interactive digital books developed by PGMI IAIN Palangka Raya students. This activity is carried out collaboratively, where students design learning media with the guidance of lecturers who also act as expert validators. The activity stage begins with the identification of needs through observations and interviews at partner schools, especially on the theme "Look Around You" in Indonesian language subjects. Students then developed interactive teaching materials that integrated text, images, audio, and other multimedia elements using digital platforms. Media validation was conducted by four expert lecturers with very feasible results: material experts (94%), design experts (96%), classroom teachers (71%), and field trials (91%). The t-test showed a significant increase in learning outcomes (t = 6.60) with an N-Gain score of 1.00 in the high category. This program shows that collaboration between lecturers and students in developing learning media can have a real positive impact on the quality of basic education and can be a sustainable model of academic empowerment.